Establishing the rate of interaction of flood risks a multi-variate analysis of hazards, exposure, and vulnerabilities as a foundation to climate change adaptation in the Philippines - Rivera-To, Theresa
The Philippines, particularly within its capital, Metro Manila, is no stranger to the problem of flooding and its consequent disasters prior to global discussions of climate change. However, rapid urbanization has provided evidences of a high correlation of increased incidences of flooding and the consequent damage to property and injury or loss of life as a result of poor planning strategies aimed towards the safety of the urban population. This paper focuses on risk-based assessments of hazards, vulnerabilities, and exposures as outlined by the risk triangle to define significant variables and relationships that affect the risk of injury to flooding. The study aims to establish a rate of percentage of risk of injury due to flooding by determining the marginal effects on significant variables through an ordered probit regression model. Ultimately, the goal is to establish the design and planning implications for urban populations within flood-prone settlements. The study was conducted on the urban areas of the Marikina River Basin particularly the cities of Marikina, Pasig and Taguig. Households lying within the residential zones as defined by their respective Comprehensive Land Use Plan were surveyed to acquire data for the study. The results of the study allowed to justify the shift from built structures to green infrastructures by determining risk-based sizes for urban river easements and no-build flood zones.